Dampak Socio-Ekonomi Standarisasi Jaminan Produk Halal Pada Usaha Mikro Dan Kecil: Dampak Socio-Ekonomi Standarisasi Jaminan Produk Halal Pada Usaha Mikro Dan Kecil - Ahmad Muttaqin; Vierri Adam Aziz (Jurnal Penelitian Agama, 2023)
This article aims to describe the social and economic impacts of implementing the Halal Product Guarantee for micro and small business groups in Purwokerto. JPH is a halal quality standard implemented by the government for goods and services distributed on the national market to provide protection to consumers who are generally Muslim. As a halal standard, JPH implements a quality system in several models according to the characteristics of the product to be guaranteed. It is in this process that micro and small business groups experience obstacles, especially at the institutional and management levels which then lead to a tendency to respond to indifference, indifference and apathy. The research uses a descriptive approach and qualitative data obtained from micro and small business groups in Purwokerto, Central Java. The analysis is based on a political economy perspective that focuses more on exploring political considerations for economic policies. The results of the study show that the response of indifference, indifference and apathy of the micro and small business groups towards JPH is not in terms of halal substance, but in technical procedures and financing. The main argument is that first, JPH is the government's obligation as part of consumer protection, so everything that arises from the management process is not the responsibility of the goods/services provider. Second, micro and small businesses do not have adequate capital capacity to strengthen their institutions. The function of micro and small businesses in the context of development is more on increasing the economic participation of citizens. Because of that, JPH is positioned as an intervention that must be carried out by the government.